Design of an allosterically modulated doxycycline and doxorubicin drug-binding protein. - Schmidt, Karin; Gardill, Bernd; Kern, Alina; Kirchweger, Peter; Börsch, Michael; Muller, Yves (Proceedings of the National Academy of Sciences of the United States of America, 2018)
The allosteric interplay between distant functional sites present in a single protein provides for one of the most important regulatory mechanisms in biological systems. While the design of ligand-binding sites into proteins remains challenging, this holds even truer for the coupling of a newly engineered binding site to an allosteric mechanism that regulates the ligand affinity. Here it is shown how computational design algorithms enabled the introduction of doxycycline- and doxorubicin-binding sites into the serine proteinase inhibitor (serpin) family member α1-antichymotrypsin. Further engineering allowed exploitation of the proteinase-triggered serpin-typical S-to-R transition to modulate the ligand affinities. These design variants follow strategies observed in naturally occurring plasma globulins that allow for the targeted delivery of hormones in the blood. By analogy, we propose that the variants described in the present study could be further developed to allow for the delivery of the antibiotic doxycycline and the anticancer compound doxorubicin to tissues/locations that express specific proteinases, such as bacterial infection sites or tumor cells secreting matrix metalloproteinases.

Structural and functional characterization of SiiA, an auxiliary protein from the SPI4-encoded type 1 secretion system from Salmonella enterica - Kirchweger, Peter; Weiler, Sigrid; Egerer-Sieber, Claudia; Blasl, Anna-Theresa; Hoffmann, Stefanie; Schmidt, Christiane; Sander, Nathalie; Merker, Dorothee; Gerlach, Roman; Hensel, Michael; Muller, Yves (Molecular Microbiology, 2019)
Salmonella invasion is mediated by a concerted action of the Salmonella pathogenicity island 4 (SPI4)-encoded type one secretion system (T1SS) and the SPI1-encoded type three secretion system (T3SS-1). The SPI4-encoded T1SS consists of five proteins (SiiABCDF) and secretes the giant adhesin SiiE. Here, we investigated structure-function relationships in SiiA, a non-canonical T1SS subunit. We show that SiiA consists of a membrane domain, an intrinsically disordered periplasmic linker region and a folded globular periplasmic domain (SiiA-PD). The crystal structure of SiiA-PD displays homology to that of MotB and other peptidoglycan (PG)-binding domains. SiiA-PD binds PG in vitro, albeit at an acidic pH, only. Mutation of Arg162 impedes PG binding of SiiA and reduces Salmonella invasion efficacy. SiiA forms a complex with SiiB at the inner membrane (IM), and the observed SiiA-MotB homology is paralleled by a predicted SiiB-MotA homology. We show that, similar to MotAB, SiiAB translocates protons across the IM. Mutating Asp13 in SiiA impairs proton translocation. Overall, SiiA shares numerous properties with MotB. However, MotAB uses the proton motif force (PMF) to energize the bacterial flagellum, it remains to be shown how usage of the PMF by SiiAB assists T1SS function and Salmonella invasion.
CRIS-Team WoS Importer:2019-10-04